Environmental engineering - Weiner, Ruth F.
This book provides a comprehensive introduction to air, water, noise, and radioactive materials pollution and its control. Legal and regulatory principles and risk analysis are included in addition to engineering principles. The text presents the engineering principles governing the generation and control of air and water pollutants, solid and hazardous waste, and noise. Water quality and drinking water treatment are discussed, as well as the elements of risk analysis. Radioactive waste generation and treatment in relation to the nuclear fuel cycle, are discussed. The health and environmental effects of all these pollutants are discussed. An introduction to the Federal laws and regulations governing pollution is included. - This text embraces the latest thinking in environmental engineering - Includes updates in regulation and current pollution abatement technologies.